Extra-Judicial Dispute Resolution and the Realization of Justice in the Indonesia Legal System - A. Dardiri Hasyim (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2021)
Abstract: Arbitration in Indonesia is governed by the Civil Code and Law No. 30 of 1999 on Arbitration. However, there are indications of disharmony between the provisions in both laws, especially related to the fulfilment of the rights of justice seekers outside the court. This paper seeks to examine the fulfilment of rights of justice seekers outside the courts contained in Law No. 30 of 1999 and in the Civil Code. This study concluded that Law No. 30 of 1999 contains 6 (six) points of fulfilment of rights in the settlement of disputes outside the court, namely: the right to choose arbitration; the right to choose a mediator/arbitrator; the right to argue; the right to determine the event of dispute resolution; the right to a verdict; and the right to deny the verdict. In contrast, some articles in the Civil Code are not in line with the provisions of Law No. 30 of 1999 given some regulations accompanying the Civil Code related to the settlement of disputes outside the court, namely: Reglement op de Rechtsvordering (Rv) and Rechtsreglement Buitengewesten (RBg). Therefore, new regulations are needed to respond to the modern development.Abstrak: Arbitrase di Indonesia didasarkan pada KUHPerdata dan UU No. 30 Tahun 1999 tentang Arbitrase. Namun demikian, terdapat indikasi adanya ketidakselarasan antara ketentuan yang ada dalam keduanya terkait pemenuhan hak para pencari keadilan di luar pengadilan. Tulisan ini berupaya mengkaji konsep pemenuhan hak bagi para pencari keadilan di luar pengadilan yang terdapat dalam UU No 30 tahun 1999 dan juga KUHPerdata. Dari kajian yang telah dilakukan diperoleh kesimpulan bahwa terdapat 6 (enam) poin pemenuhan hak dalam penyelesaian sengketa di luar pengadilan yang tertuang dalam UU No. 30 Tahun 1999, yaitu: hak memilih arbitrase; hak memilih mediator/arbiter; hak berpendapat; hak menentukan acara penyelesaian sengketa; hak mendapat putusan; dan hak menyanggah putusan. Di sisi lain, terdapat pasal-pasal dalam KUHPerdata yang belum selaras dengan tuntutan UU No. 30 Tahun 1999 dikarenakan telah ada peraturan yang menyertai KUHPerdata berkaitan dengan penyelesaian sengketa di luar pengadilan, yaitu: Reglement op de Rechtsvordering (Rv) dan Rechtsreglement Buitengewesten (RBg). Untuk itulah diperlukan peraturan baru yang mampu menjawab perkembangan zaman.